Foraging ecology of common dolphins (Delphinus sp.) in the Hauraki Gulf, New Zealand : a thesis presented in fulfilment of the requirements for the degree of Master of Science (Zoology), Massey University, Albany, New Zealand - Burgess, Elizabeth A (Massey University, 2006)
This study investigated the foraging ecology of common dolphins (Delphinus sp.) in the Hauraki Gulf Marine Park, off the east coast of Auckland. New Zealand. Like most species of small cetacea in the Southern Hemisphere, its foraging habits are poorly described. A total of 59 focal group follows of common dolphins were conducted between January and April 2006. Observations were conducted at the surface, recording the predominant behavioural state of the group, foraging phase, foraging strategy, group dispersion, group formation, swimming style, group heading, calf presence and associated species. All occurrences of fission-fusion events and surface behaviours were recorded. This study tested the hypothesis that foraging behaviour of common dolphins would be influenced by environmental and physical parameters, group size, calf presence and associations with other species. In the Hauraki Gulf, foraging behaviour was recorded during all common dolphin follows, with 14% ± 1.7 (mean ± s.e.) of time spent feeding. Larger groups of dolphins spent more time foraging than smaller groups. Herding accounted for a large part of the foraging behaviour of common dolphins (mean ± s.e. = 28% ± 2.3. n = 54). Larger groups were found to spend significantly more time herding than smaller groups. Herding was generally directed towards the nearest landmass. Common dolphins use a variety of foraging strategies, both individual and group coordinated strategies. High-speed pursuits (n = 29) and kerplunkmg (n= 15) were the only individual foraging strategies recorded. Coordinated feeding strategies employed were synchronous diving (n = 50), Ime-abreast (n = 28), carouselling (n = 26) and wall-formation (n = 4). Synchronous diving and carouselling were the most enduring strategies, accounting for a significant proportion of foraging behaviour (mean ± s.e. - 32% ± 0.05 and 24% ± 0.08 of instantaneous samples, respectively). Foraging strategies were typified by vanous group formations, dispersion between group members, swimming styles and breathing intervals. Foraging strategies were also observed to have different roles in dolphin foraging. Line-abreast and wall- formation were associated with herding. However, high-speed pursuit, kerplunking and carouselling were strategies synonymous with feeding. Foraging strategies were shown to be dynamic, with dolphin groups changing strategies within a foraging bout (mean ± s.e. = 3 ± 0.4). Larger groups spent more time engaged in coordinated foraging strategies than smaller groups. Noisy surface behaviours and fission-fusion events were frequently seen in synchrony with foraging behaviour. Calves present in a foraging group, typically assumed a central position in the group during herding, but remained on the periphery during feeding. When feeding, common dolphins frequently were associated with Australasian gannets (Morus senator), shearwaters (Puffinus spp.) and Bryde's whales (Balaenoptera brydei) Observations on the predatory behaviour of each species suggested a temporary close association between birds, whales and dolphins. This study showed an association of Australasian gannet flocks (n =46) and Bryde's whales (n = 27) with common dolphins, and described the nature of the joint aggregations of mixed-species feeding in the Hauraki Gulf. The behaviour of gannots and whales strongly coincided with that of the foraging dolphin group. Whales were recorded tracking behind foraging dolphins for up to one and a half hours (mean ± s.e. = 23 min ± 2.3). Observations suggest that the relationship between gannets and whales with common dolphins was deliberate, and that these species take advantage of the superior ability of dolphins to locate and concentrate prey. The associations with gannets and whales had a significant impact on common dolphin foraging behaviour. Duration of the phenomenon was predicted to be a direct function of the quantity of prey fish available. The presence of a whale had a sizable impact on the diffusion of feeding aggregations. Results from this study indicate that the benefits of coordinated team hunts implemented by common dolphins in the Hauraki Gulf are a key factor in their foraging ecology. Their cooperative foraging skills appear to not only benefit the common dolphin individual, but other species as well. Ultimately, their role as a social hunter and an abundant, apex predator in the ocean, suggests that the common dolphin is a strongly interacting species which may facilitate population viability of other species in the Hauraki Gulf ecosystem.
Keywords: New Zealand Hauraki Gulf; Common dolphin; Behavior; Food; Ecology